1988
DOI: 10.1016/0014-2999(88)90094-5
|View full text |Cite
|
Sign up to set email alerts
|

μ-, δ- and κ-opioid receptor-mediated inhibition of neurotransmitter release and adenylate cyclase activity in rat brain slices: studies with fentanyl isothiocyanate

Abstract: We investigated the effects of [D-Ala2,D-Leu5]enkephalin (DADLE). [D-Ala2,MePhe4,Gly-ol5]enkephalin (DAGO), [D-Pen2,D-Pen5]enkephalin (DPDPE) (0.01-1 microM) and bremazocine (0.001-0.3 microM) on the electrically evoked release of radiolabelled neurotransmitters and on the dopamine (DA)-stimulated cyclic AMP efflux from superfused rat brain slices. The differential inhibitory effects of these agonists on the evoked neurotransmitter release indicate that the opioid receptors mediating presynaptic inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 29 publications
4
53
0
Order By: Relevance
“…Mulder et al (1984) found that lower doses of dynorphin A (1-13) inhibited both the spontaneous efflux of tritium and the potassium-induced release of [3H]-dopamine from rat striatal slices, whereas the release of ['4C]-acetylcholine was not significantly affected. Similar effects were also reported with administration of the selective K-agonist, U 50,488H, at concentrations below 1 ,IM (Schoffelmeer et al, 1988). Previously, we reported that the dose of dynorphin A (1-13) tested in this study did not alter dopamine release in the striatum, whereas higher doses of this peptide (2.5 and 5 nmol per rat, i.c.v.)…”
Section: Resultssupporting
confidence: 62%
“…Mulder et al (1984) found that lower doses of dynorphin A (1-13) inhibited both the spontaneous efflux of tritium and the potassium-induced release of [3H]-dopamine from rat striatal slices, whereas the release of ['4C]-acetylcholine was not significantly affected. Similar effects were also reported with administration of the selective K-agonist, U 50,488H, at concentrations below 1 ,IM (Schoffelmeer et al, 1988). Previously, we reported that the dose of dynorphin A (1-13) tested in this study did not alter dopamine release in the striatum, whereas higher doses of this peptide (2.5 and 5 nmol per rat, i.c.v.)…”
Section: Resultssupporting
confidence: 62%
“…Slices (0.3 ϫ 0.3 ϫ 1 mm) were prepared using a McIlwain tissue chopper. For each experiment, brain slices from six animals were pooled, then incubated with radiolabeled DA, NE, or 5-HT as described previously (Schoffelmeer et al, 1988). In short, slices were washed twice with 5 ml of Krebs-Ringer's bicarbonate medium containing the following (in mM): 121 NaCl, 1.…”
Section: Methodsmentioning
confidence: 99%
“…In replicate experiments, brain tissue was sliced (0.3 Â 0.3 Â 2 mm) and for each brain region the slices of two animals were pooled. Subsequently, brain slices were incubated and superfused as described before (Schoffelmeer et al, 1988). Briefly, slices were incubated for 15 min in Krebs-Ringer bicarbonate containing 5 mCi [ 3 H] dopamine (Radiochemical Centre, Amersham, Buckinghamshire, UK) in an atmosphere of 95% O 2 -5% CO 2 at 371C.…”
Section: Neurotransmitter Releasementioning
confidence: 99%